Bacterial antimicrobial resistance and dermatological ramifications. (12th April 2022) - Muhaj, Fiorinda F.; George, Saira J.; Tyring, Stephen K.
Summary: The spread of COVID‐19 serves as a reminder of the might of microbes in the era of modern medicine. For years, another threat has preoccupied infectious disease experts and public health officials alike: rising antimicrobial resistance (AMR). Resistance is exceeding stewardship efforts as well as the rates of new drug development and approval in the market. A dry antimicrobial pipeline is threatening regression to a preantibiotic era. While the consequences of resistance may seem far removed from daily clinical practice, awareness of AMR is essential to dermatological care given that dermatologists prescribe more antibiotics per physician than other providers. Antibiotics in dermatology are often used for prolonged courses, with significant potential for microbiome alteration and antibiotic‐related adverse effects. Through this review we hope to contribute to efforts of bringing the crisis of AMR to the forefront of daily dermatological practice. Abstract : Antimicrobial resistance is exceeding stewardship efforts and the rates of new drug development and approval in the market. Dermatologist are among the most common prescribers of oral and topical antibiotics, making antimicrobial resistance a prime concern in daily practice. Through this review of dermatologically relevant pathogens and innovative therapeutics, we hope to further contribute to efforts of bringing the crisis of resistance to the forefront of dermatological practice. Plain language summary available online